Inquiry Model: How to Improve the Ability of the Nature of Science and Its Aspects in Elementary School? - Kelana, Jajang Bayu; Robandi, Babang; Widodo, Ari (International Journal of Elementary Education, 2022)
The nature of science and is something that is very important to be taught in elementary schools. In the field there are not many studies that involve learning models in an effort to develop the nature of science, both from the dimension its aspects and the nature of science itself. The purpose of this research is to reveal how the inquiry model affects the ability of the nature of science and its aspects of students in elementary school. The method used is quantitative with a pre-experimental pre-test and post-test one group design. The subjects of this study were fifth grade elementary school students with a sample of 36 students. The instruments in this study used test questions (products), student observation sheets (process) and questionnaires (attitudes). The results showed that the P-value = 0,000 < 0,05. So H1 is accepted. Thus, learning with the inquiry model significantly increases the product dimensions (cognitive) of students in elementary schools. The measurement of process dimensions through observation has an average value of 58.2% and is in the sufficient category. To measure the dimensions of attitude using a questionnaire in measuring the 10 basic properties its aspects, data analysis is on good criteria. In general, the inquiry model can have an influence on the ability of the nature of science and its aspects of students in elementary schools. For further research, it can be developed using other models/approaches/strategies/methods, in order to improve students' ability to the nature of science and its aspects.